TBAJ-876 displays bedaquiline-like mycobactericidal potency without retaining the parental drug’s uncoupler activity - Sarathy, Jickky Palmae (2020)
The diarylquinoline F1FO-ATP synthase inhibitor bedaquiline (BDQ) displays protonophore activity. Thus, uncoupling electron transport from ATP synthesis appears to be a second mechanism of action of this antimycobacterial drug. Here, we show that the new BDQ analogue TBAJ-876 did not retain the parental drug’s protonophore activity. Comparative time-kill analyses revealed that both compounds exert the same bactericidal activity. These results suggest that the uncoupler activity is not required for the bactericidal activity of diarylquinolines.